PENGARUH ETIKA KEPEMIMPINAN, FUNGSI BADAN PENGAWAS, KAPASITAS SUMBER DAYA MANUSIA DAN KOMITMEN ORGANISASI TERHADAP KUALITAS PELAPORAN KEUANGAN PADA LEMBAGA PERKREDITAN DESA (LPD) SE- KOTA DENPASAR - Ni Made Anggreni (UNHI Press, 2021)
Financial reporting quality has an important meaning for the company, which provides information about the financial condition needed by users to make decisions. The purpose of this study was to determine the effect of leadership ethics, the function of the supervisory body, human resource capacity and organizational commitment to the quality of financial reporting at Lembaga Perkreditan Desa on Denpasar City. The population in this study were all employees who worked on LPD Denpasar City, 144 respondents were used, consisting of the Head of the LPD, the supervisory body, the secretary and treasurer. The sampling method used was purposive sampling technique. Based on the results of the study, it was found that the variables of leadership ethics, human resource capacity and organizational commitment had a positive effect on the quality of financial reporting, while the function of the supervisory body had no effect on the quality of financial reporting in LPD on Denpasar City.